Drought effects on tree growth, water use efficiency, vulnerability and canopy health of Quercus variabilis-Robinia pseudoacacia mixed plantation - Jia, HanSen; Guan, ChongFan; Zhang, JinSong; He, ChunXia; Yin, ChangJun; Meng, Ping (Frontiers in Plant Science, 2022)
Drought-induced forest canopy die-back and tree mortality have been commonly recorded in the lithoid mountainous regions of northern China. However, the capacity of trees to regulate their carbon and water balance in response to drought remains inadequately understood. We measured tree growth, intrinsic water use efficiency (iWUE), vulnerability, and canopy health during drought events using dendrochronology, C isotope measurements, and a tree canopy health survey in a mixed plantation of Quercus variabilis and Robinia pseudoacacia. Resistance (Rt), recovery (Rc), resilience (Rs), and increased amplitude in iWUE compared to the indices 3 years before drought (iWUEr) were calculated for each species across the dominant tree (D), co-dominant tree (CD), and suppressed tree (S). Our results revealed that D and CD showed lower Rt, higher Rc, and higher iWUEr than S. After exposure to multiple sequential drought events, Q. variabilis showed an increasing trend in Rt, and R. pseudoacacia showed a decreasing trend in Rc. R. pseudoacacia exhibited a more conservative strategy towards drought, resulting in a negative SRt-iWUEr (slope of the linear model fitted to capture the trend between Rt and iWUEr) during drought events than Q. variabilis. For individual trees, lower Rc or positive SRt-iWUEr Q. variabilis and negative SRt-iWUEr R. pseudoacacia were more susceptible to canopy die-back. In conclusion, our study offers a new perspective for improved management practices in the design of silvicultural actions for forestry plantations in lithoid mountainous areas with increasing drought risk.